2016
DOI: 10.1016/j.ocecoaman.2016.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Climate teleconnections and indicators of coastal systems response

Abstract: This article surveys secular urban sandy beaches erosion-accretion and its relationship with climate teleconnections, e.g., El Niño Southern Oscillation (ENSO), Atlantic Multidecadal Oscillation (AMO), and extreme events, e.g., storm surges, great rivers' floods, and heavy rains in adjacent basins. The paper aims to discuss these issues and the expected coastal retreat as a consequence of manmade climate changes, e.g., sea level rise (SLR) and increased storminess in the coming decades. Several beaches (Buceo,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
29
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 37 publications
1
29
0
2
Order By: Relevance
“…However, Verocai et al (2015) found a slight increase in the occurrence of events greater than 1.89 m AMSL, capable of modifying the coastal morphology, over the last decade. At the same time, a fluctuating trend in atmospheric energy has been observed, verified by storm surges with maximums at the beginning of the 20 th century and minimums between 1960 and 1970, and an increasing trend of the average energy since then, assimilable to the AMO variability (Gutiérrez et al, 2016). Higher intensity and frequency of storm surges and SLR would determine a highly erosive scenario for the coast of Montevideo (Orlando et al, 2019).…”
Section: Resultsmentioning
confidence: 91%
See 4 more Smart Citations
“…However, Verocai et al (2015) found a slight increase in the occurrence of events greater than 1.89 m AMSL, capable of modifying the coastal morphology, over the last decade. At the same time, a fluctuating trend in atmospheric energy has been observed, verified by storm surges with maximums at the beginning of the 20 th century and minimums between 1960 and 1970, and an increasing trend of the average energy since then, assimilable to the AMO variability (Gutiérrez et al, 2016). Higher intensity and frequency of storm surges and SLR would determine a highly erosive scenario for the coast of Montevideo (Orlando et al, 2019).…”
Section: Resultsmentioning
confidence: 91%
“…These beaches show a behaviour that responds to interannual ENSO-related variability, in particular, recovery (progradation and increase in sand volume) during El Niño events, and erosion related to the occurrence of strong La Niña events. During La Niña years there is a higher incidence of strong winds from the South and particularly from the SW, while during the El Niño years the winds from N, E to ESE increase (Gutiérrez et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations